Physical modeling of jointed bedrock erosion by block quarrying - Dubinski, Ian Michael, author; Wohl, Ellen E., advisor (Colorado State University. Libraries, 2009)
The primary objective of this dissertation is to provide insight in erosional processes, types of channel geometry, and relative rates of incision and knickpoint retreat of channels formed on jointed, resistant rock in a controlled experimental flume setting. Jointed, resistant rock occurs primarily in crystalline lithologies such as granite, gneiss, quartzite, and basalt. These lithologies can be found in a wide range of climatic and tectonic settings. Channels in jointed bedrock may have distinctive erosional processes and geometry relative to channels formed in unjointed bedrock. Joints, fractures, and other discontinuities such as bedding planes in the bedrock are locally weakly resistant zones in contrast to the resistance of unjointed bedrock. These areas may be preferentially weathered to form weakly or completely detached blocks that may be mobilized by flows in the channel. Channels in jointed bedrock commonly have abrupt lateral or downstream discontinuities in bed elevation including steps and knickpoints. A physical model of jointed bedrock using concrete divided into discrete blocks was constructed in a flume and allowed to erode over time by primarily block quarrying. Experimental controls examined in the flume included discharge, channel width, and joint spacing. Observed changes in planform geometry were retreat of the downstream knickpoint with no development of anabranching channels. Erosion by block quarrying occurred with variation between runs of differing control variables. A force analysis of block quarrying combined with a statistical analysis of the erosion results in conjunction with the control variables, including joint spacing and stream power, provided insight into the process of block quarrying. Wider vertical joint spacing produced more easily eroded blocks than a narrower joint spacing with equal block height in each case when friction forces along the side of the blocks are considered. As blocks loosen over time, the side forces diminish. Without side forces resisting motion, blocks formed by the wider vertical joint spacing are less easily mobilized than the smaller blocks. The other important element in defining block erosion is the key block concept. Erosion of blocks occurred as either a few blocks at one time or a mass movement of blocks at roughly the same time. Mass movements sometimes occurred after removal of a few blocks. These movements of a few blocks were termed key block movements and formed a bimodal population in terms of event magnitude with the mass movements as the other sub-population. Comparison with joint spacing field data from observed anabranching, inner channel, and transitional reaches along the Orange River in South Africa generally concurred with the conclusions drawn from analysis of the model results. Block quarrying is controlled by the balance between block mobility and hydraulic conditions that change over time with periods of little block movement punctuated by mass movements.
Keywords: bedrock erosion; jointed bedrock; knickpoints; quarrying; geology; geological; geomorphology; geological engineering